(untitled) (Fiep Bulletin - online, 2011)
This study investigated the cognitive response to questions concerning the basic mental elementary math calculations, when placed in the context of the practice of a game adapted from the rules of Korfebol, developed as part of Physical Education. The individuals are students of both genders, aged between 11 and 15 years enrolled in 6th grade at a official learning institution. Two tests were used; Test1 had the objective of determining the level of competence of the answers given to questions about basic mathematical calculations, performed by the method of questioning. Soon after, the Test2 was applied, where the mathematical calculation were inserted in the practice of the game. We adopted the method of participant observation and content analysis together with quantitative analysis.The results show that 95.2% of individuals have benefited by way of questioning the applicability of mathematical questions from Test2. Thus, the findings suggest that ludic sport game context influenced positively the cognitive response to questions of the math calculations of the children who participated in the experiment.